Verbo e cor: relações intermidiáticas na obra de Almada Negreiros - Carla Cristina de Araujo (2015)
This thesis focuses on the interart relations and the modalities ofintermediality proposed by Irina Rajewski and others, on the work of thePortuguese multi-artist Almada Negreiros, who was a poet, short story writer,playwright, painter, designer, cartoonist, stain glass and tapestry maker, actor,choreographer, dancer, costume designer, among other skills. In addition to hisartistic creation, he was also an essayist, art critic and scholar of mathematics andgeometry, which led him to create part of his work based on calculations. Heappeared in the Portuguese art scene in the early years of the tumultuous twentiethcentury and played a key role in the literary and artistic renewal that changed thesocial and cultural landscape of Portugal. A brief reflection on his artistic activitiesin Portugal is therefore directly related to interart studies and modalities ofintermediality. His literary texts and paintings are analyzed in the light of theirinterrelationships as well as their relation to other arts, such as theater and music.